Endurance training induces apoptosis in the tumor mass in the C26-bearing mouse model - Barone, Rosario; Macaluso, Filippo; D’Amico, Daniela; Gargano, Caterina; Hassani, Medhi; Xue, Zhigang; Cappello6, Francesco; Zummo, Giovanni; Adamo, Sergio; Farina, Felicia; Coletti, Dario; Di Felice, Valentina (Italian Journal of Anatomy and Embryology, 2018)
Cachexia, sarcopenia and anorexia are characterised by muscle wasting. This condition is a weakening, shrinking, and loss of muscle caused by a disease or lack of use. The loss of muscle causes a decrease in strength and inability to move compromising the quality of life. Recently we demonstrated that the skeletal muscle of endurance trained Balb/c mice release IL-6 and Hsp60 (inside exosomes) in the blood stream. We studied the expression of Hsp60 in the muscles of trained and untrained C26-bearing mice, to understand if Hsp60 was over-expression may improve muscle performance and reduce cachexia. Four different interleukins have been also studied in cachectic mice, to under- stand which was their effect on Hsp60 expression both in the tumor mass and the trained mus- cle. In the present study we demonstrated that: 1) IL-6 is released by the trained muscle; 2) IL-6 is release also by the tumor mass, 3) in animals inoculated with the C26 tumor and trained after inoculation, IL-6 is synthesized mainly by the skeletal muscle and the tumor mass undergo apoptosis. This work was funded by PRIN2012 - Prof. Farina F.